2013
DOI: 10.1139/apnm-2012-0302
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of oxidative stress and tissue damage released by muscle and liver after a single bout of swimming exercise

Abstract: Both acute exercise and excessive training can cause oxidative stress. The resulting increase in free radicals and the inadequate response from antioxidant systems can lead to a framework of cellular damage. An association between affected tissue and the biomarkers of oxidative stress that appear in plasma has not been clearly established. The aim of this study was to evaluate the source of oxidative stress biomarkers found in the plasma of untrained rats after a single bout of swimming exercise at 2 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 40 publications
5
27
0
2
Order By: Relevance
“…On the other hand, swimming exercise with moderate intensity for 10 weeks has no effect on serum TAC [68] . Also, there were no significant changes in TAC in the plasma of rats after swimming exercise at 2 different intensities; low intensity or high intensity [69] . Although it appears contradictory, these data suggest that for this specific variable (TAC), exercise type is more important than intensity.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, swimming exercise with moderate intensity for 10 weeks has no effect on serum TAC [68] . Also, there were no significant changes in TAC in the plasma of rats after swimming exercise at 2 different intensities; low intensity or high intensity [69] . Although it appears contradictory, these data suggest that for this specific variable (TAC), exercise type is more important than intensity.…”
Section: Discussionmentioning
confidence: 80%
“…This feature is also closely related to exercise intensity (Loegering 1974, Ramos et al 2013; however, these results are not observed in the C-Ex offspring indicating raised cellular stress resistance (Jeong et al 2012). Higher levels of plasma LDH in the Bro-Ex rats suggest an impaired capacity of cell membrane adaptation to chronic exercise load besides other positive responses in adiposity, lipid profile, thyroid status, and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 88%
“…Through providing a quantifiable characteristic of a biological process, biomarkers can be used as a clinical surrogate endpoint [10], or provide objective information regarding the effect of an exercise protocol [11][12][13][14] or clinical treatment [15][16][17]. In addition, they can aid in understanding the prediction, cause, diagnosis, progression, regression, or outcome of treatment of disease [8], or in the context of this review, the acute and chronic psychophysiological stress response to exercise.…”
Section: What Is a Biomarker?mentioning
confidence: 99%